2016
DOI: 10.4269/ajtmh.16-0007
|View full text |Cite
|
Sign up to set email alerts
|

Anisakiasis Causing Acute Dysentery in Malaysia

Abstract: Abstract. Human anisakiasis is a zoonosis acquired by eating raw or undercooked infected seafood. Herein, we report a case of acute dysentery caused by anisakiasis in a 64-year-old man in Malaysia. A colonoscopy was performed and a nematode larva was found penetrating the mucosa of the ascending colon. Bleeding was observed at the site of penetration. Y-shaped lateral epidermal cords were seen from the cross section of the worm, which is a prominent feature of Anisakis larva. Molecular analysis using polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The worldwide adoption of different cuisine, growth of better tools for diagnosis and greater knowledge on Anisakis and its infection, has resulted in significantly increased reporting of anisakiasis. Other countries in which cases of anisakiasis have been reported include Korea (Sohn et al, 2015), China (Qin et al, 2013), Malaysia (Amir et al, 2016), Taiwan (Li et al, 2015), the United Kingdom (Audicana and Kennedy, 2008), Spain (Herrador et al, 2018). , Italy (Mattiucci et al, 2018; Guardone et al, 2018), France (Audicana and Kennedy, 2008), Germany (Audicana and Kennedy, 2008), Denmark (Andreassen and Jorring, 1970), Norway (Jacobsen and Berland, 1969), Croatia (Mladineo et al, 2016), the United States of America (Kojima et al, 2013), Southern America (Borges et al, 2012; Eiras et al, 2018), Egypt (Audicana and Kennedy, 2008), South Africa (Audicana and Kennedy, 2008), and Australia (Shamsi and Butcher, 2011), implying anisakiasis occurrence in all continents of the globe excluding Antarctica.…”
Section: Epidemiologymentioning
confidence: 99%
“…The worldwide adoption of different cuisine, growth of better tools for diagnosis and greater knowledge on Anisakis and its infection, has resulted in significantly increased reporting of anisakiasis. Other countries in which cases of anisakiasis have been reported include Korea (Sohn et al, 2015), China (Qin et al, 2013), Malaysia (Amir et al, 2016), Taiwan (Li et al, 2015), the United Kingdom (Audicana and Kennedy, 2008), Spain (Herrador et al, 2018). , Italy (Mattiucci et al, 2018; Guardone et al, 2018), France (Audicana and Kennedy, 2008), Germany (Audicana and Kennedy, 2008), Denmark (Andreassen and Jorring, 1970), Norway (Jacobsen and Berland, 1969), Croatia (Mladineo et al, 2016), the United States of America (Kojima et al, 2013), Southern America (Borges et al, 2012; Eiras et al, 2018), Egypt (Audicana and Kennedy, 2008), South Africa (Audicana and Kennedy, 2008), and Australia (Shamsi and Butcher, 2011), implying anisakiasis occurrence in all continents of the globe excluding Antarctica.…”
Section: Epidemiologymentioning
confidence: 99%
“…and butterfly wing shape for Pseudoterranova spp. (Lauwers et al, 2017); the specification of this structure in human medicine has been reported for hepatic anisakiasis due to Pseudoterranova decipiens (Murata et al, 2018), A. pegreffii, and A. simplex in cases of dysentery (Amir et al, 2016). In fish, only Laffon-Leal et al (2000) reported the genus Contracaecum spp.…”
Section: Discussionmentioning
confidence: 99%
“…Anisakidosis is a globally distributed disease caused by the consumption of marine animals, mainly poorly cooked or raw fish due to the acquisition of new gastronomic habits from different cultures (Tokiwa et al, 2018). When the parasite is ingested alive it has the ability to survive for a short period of time in the human body and can adhere to various tissues, such as the esophagus, stomach, duodenum, jejunum, ileum, or colon, generating a primary inflammatory response (Amir et al, 2016). Clinical manifestations include moderate or severe allergies, angioedema, hypotension, bronco spasms, anaphylactic shock, and asthma (Nieuwenhuizen & Lopata, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…simplex s.s has been described more frequently in countries where the consumption of raw fish meat is a culinary tradition, such as in Japan, Peru and Mexico [ 119 ]. More than 90% of the zoonosis cases reported in humans have been in Japan, about 2000 cases/year being registered [ 120 , 121 , 122 , 123 ]. In Europe, 500 cases/year are reported, in Germany, France, Spain and the Netherlands [ 124 , 125 , 126 ] ( Table 2 , Figure 3 ).…”
Section: Geographical Distributionmentioning
confidence: 99%